Comparison of process control viruses for use in extraction and detection of human norovirus from food matrices. (November 2015) - Gentry-Shields, Jennifer; Jaykus, Lee-Ann
Abstract: Although RT-qPCR is a powerful tool for human norovirus (HuNoV) detection, low virus concentrations in potentially large sample volumes necessitate the use of inefficient sample processing step(s) prior to detection. Process control viruses (PCVs) are used to monitor the efficiency of these virus concentration steps. This study compared five PCVs [Mengovirus (Mengo), murine norovirus (MNV-1), MS2 coliphage, Tulane virus, and turnip crinkle virus (TCV)] to two HuNoV strains for recovery during the steps of elution, polyethylene glycol precipitation (PEG), and RNA extraction from select foods (lettuce and sliced deli ham). Results demonstrate high recovery efficiencies of HuNoV GI.6 and GII.4 using the methods described in this study: combined (sequential) losses during processing from sliced deli ham and lettuce were < 1 log10 genome equivalent copies (GEC). When considering the processing steps separately, HuNoV loss was negligible after elution, and low after PEG precipitation (mean 0.5 log10 GEC) and RNA extraction (mean 0.1 log10 GEC). The virus that least mimicked the behavior of HuNoV during sample processing was MNV-1. Of the viruses tested, a commercial mengovirus strain gave recovery efficiencies closest to HuNoV, showing combined losses from sliced deli ham and lettuce of < 1 log10 GEC and 1 log10 GEC, respectively. All PCVs do not behave equivalently and validation of their performance is recommended before their routine use on an application-by-application basis. Highlights: HuNoV losses were < 1 log10 genome equivalent copies (GEC). MNV-1 least mimicked the behavior of HuNoV during sample processing. Commercial mengovirus gave recovery efficiencies closest to HuNoV.